-4.3-3z-2.9-z=-3z+5.7

Simple and best practice solution for -4.3-3z-2.9-z=-3z+5.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4.3-3z-2.9-z=-3z+5.7 equation:


Simplifying
-4.3 + -3z + -2.9 + -1z = -3z + 5.7

Reorder the terms:
-4.3 + -2.9 + -3z + -1z = -3z + 5.7

Combine like terms: -4.3 + -2.9 = -7.2
-7.2 + -3z + -1z = -3z + 5.7

Combine like terms: -3z + -1z = -4z
-7.2 + -4z = -3z + 5.7

Reorder the terms:
-7.2 + -4z = 5.7 + -3z

Solving
-7.2 + -4z = 5.7 + -3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '3z' to each side of the equation.
-7.2 + -4z + 3z = 5.7 + -3z + 3z

Combine like terms: -4z + 3z = -1z
-7.2 + -1z = 5.7 + -3z + 3z

Combine like terms: -3z + 3z = 0
-7.2 + -1z = 5.7 + 0
-7.2 + -1z = 5.7

Add '7.2' to each side of the equation.
-7.2 + 7.2 + -1z = 5.7 + 7.2

Combine like terms: -7.2 + 7.2 = 0.0
0.0 + -1z = 5.7 + 7.2
-1z = 5.7 + 7.2

Combine like terms: 5.7 + 7.2 = 12.9
-1z = 12.9

Divide each side by '-1'.
z = -12.9

Simplifying
z = -12.9

See similar equations:

| -8m-8n+p-2=-10n-9p+8 | | 12*x^2-4=0 | | t(2t+-1)=1 | | 10-(4x-1)=8-5x | | 7x+21(2x-3)=180 | | 8c*3c= | | 3x+22x-4=5(5x+6) | | (-7b+4a)+(-6a-9b)= | | 5w^2+39w+5y=0 | | 9a+19=100 | | X^2-2x+528=0 | | 98=-2(-8x+8) | | 8cos^2x-4cosx-2=0 | | 6g=6g+-34 | | 3x+x+7=6x-2x+7 | | 0.25d+6=11 | | =5x | | N-3.5=6.5 | | 9f+15=15 | | (xy^2+y)dx+(x^2y-x)dy=0 | | 3+x/2=10 | | 8=4(b-2)+4 | | 32=-5x-8 | | 12(2p+11)=12(2p+12) | | 4x+12x-7=4(4x+9) | | -1=-2y+7 | | -15=9-8x | | 8=(b-2)+4 | | 5-6(2+6)=b-14 | | 4.75m+15=2.75m+6 | | -4(x+1)+3(3x-3)=4(x-4)+12 | | 2n+8=5n-10 |

Equations solver categories